Effectiveness of transoral laser microsurgery for precancerous lesions and early glottic cancer guided by analysis of voice quality. Issue 6 (30th July 2013) - Bahannan, Abdulrahman Ali; Slavíček, Aleš; Černý, Libor; Vokřal, Jan; Valenta, Zdenek; Lohynska, Radka; Chovanec, Martin; Betka, Jan
ABSTRACT Background The purpose of this study was to show our comparison of the quality of voice obtained after superficial transoral endoscopic cordectomies (types I, II, and III) according to the European Laryngological Society classification versus the more extended cordectomy (types IV and V) among patients with glottic precancerous lesions or early glottic cancer. Methods Sixty‐two patients underwent vocal assessment after cordectomy (types I–V) for dysplasia, Tis, T1a, T1b, and T2 lesions. Results Cordectomy (types I–III) had good vocal outcomes. Cordectomy (types IV–V) showed less favorable outcomes, p < .005 in common parameters of voice range profile and symmetry in stroboscopy after cordectomy (types IV–V), with significant voice handicap index. Recurrences were found in 4 patients with T1b and T2 cancer. Two cases were managed by a higher type of cordectomy, and the other 2 by total laryngectomy. Conclusion Effect of transoral laser microsurgery on quality of voice depends on the type of cordectomy and the site of the lesion. © 2013 Wiley Periodicals, Inc. Head Neck 36: 763–767, 2014